2020
DOI: 10.23887/jet.v4i3.27101
|View full text |Cite
|
Sign up to set email alerts
|

Comic Media Assisted SQ3R Method Influence Students Comprehensive Reading Skills

Abstract: This research is motivated by students' reading skills that are not optimal and learning activities are less active and interesting. This study was aimed at recognizing the influence of SQ3R comic assisted method application to the comprehensive reading skills in the learning process of Indonesian of the fifth grade. Quasi-experiment with a non-equivalent control group design was conducted in this study. The populations of this study involved 248 students and the obtained sample involved 35 students of the fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Comic learning media has been widely researched, such as research on comics in digital form is also useful in improving students' creative thinking (Putra & Iqbal, 2004). Another study showed that comics effectively read Indonesian understanding in grade V elementary school (Dewi, Ganing, & Wayan, 2020). The development of comics is also used for various mathematical learning materials, including flat-build geometry (Kurniati, Rahimah, & Rusdi, 2017), fractions (Nova & Yunianta, 2018) to solve mathematical problems (Gumilang & Indarini, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Comic learning media has been widely researched, such as research on comics in digital form is also useful in improving students' creative thinking (Putra & Iqbal, 2004). Another study showed that comics effectively read Indonesian understanding in grade V elementary school (Dewi, Ganing, & Wayan, 2020). The development of comics is also used for various mathematical learning materials, including flat-build geometry (Kurniati, Rahimah, & Rusdi, 2017), fractions (Nova & Yunianta, 2018) to solve mathematical problems (Gumilang & Indarini, 2019).…”
Section: Introductionmentioning
confidence: 99%